(untitled) (Tanzania Medical Journal, 2009)
Aim: Objective of the study was to find out the effect of Heinsia Crinata extract (HC Et) on experimental diabetes, and hyperlipidemia in rats. Method: Ethanolic extract of Heinsia Crinata administered orally and effect of different doses of the extract on blood glucose, glucose-6- phosphatase , serum and tissue lipids in rats with alloxan induced diabetes were studied. Chlopropamide was used as standard reference drug. Ethanolic extract of Heinsia Crinata (HC Et ) at doses of 150,300,500, mg/kg body weight have been administered for present study. Results: Results indicated that the aqueous extract of HeinsiaCrinata exhibited anti-diabetic activity. Studies results indicated ,the extract suppressed the elevated glucose and in antihyperlipidemic studies, lipid levels changed in diabetic rats treated with HC Et. Conclusion: Our findings shows that extract possesed and antidiabetic activities. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 24-27